Learning From a Fly's Wing: Building a Dialogical Paradigm of Science and Islam in Science Education - Zubaidi; Dinar Maftukh Fajar; Mohammad Wildan Habibi (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2025)
The hadith narrative regarding flies—stating that one wing carries disease while the other carries an antidote—presents a contradiction that necessitates scientific study to support the integration of Islam and science in education. This experimental study employed a completely randomized design with four treatments and seven replicates to assess the inhibitory effect of housefly (Musca domestica) body parts on Salmonella typhi growth in vitro. The results demonstrated that fly wings provided significantly higher growth inhibition (p < 0.05) than other body parts and the control. However, no significant difference was found between the right and left wings (p > 0.05). These findings establish an epistemological framework for science education through a